Catheter ablation of long-standing persistent atrial fibrillation: the ugly type of AF?. (24th May 2021) - Couto Pereira, S; Rodrigues, T; Brito, J; Silverio Antonio, P; Valente Silva, B; Alves Da Silva, P; Barreiros, C; Lima Da Silva, G; Carpinteiro, L; Cortez-Dias, N; Pinto, FJ; De Sousa, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: In atrial fibrillation (AF) patients (pts), catheter ablation (CA) by isolating pulmonary veins (PVI) is the most effective therapeutic option in order to maintain sinus rhythm. The success rate of CA relies on type and duration of AF, being more successful in pts with paroxysmal AF and presenting suboptimal success in pts with long-standing persistent AF (LSPAF, >12 months). Purpose: To evaluate the success of AF ablation, particularly in LSPAF. Methods: Single-center prospective study of pts submitted to CA between 2004 and 2020. The strategy, regardless of the type of AF, was based on PVI, complemented by cavo-tricuspid isthmus line (CTI) in pts with history of flutter. Additional CA strategies were selectively considered in pts with stable atypical flutter conversion, persistent triggers or no electrograms in the VPs. Pts were monitored with Holter/7-day event loop recorder (3, 6, 12 months and annually up to 5 years). Success was assessed from the 90th day after ablation, with the absence of recurrences of any sustained atrial arrhythmias (> 30 sec). Cox regression and Kaplan-Meier survival were used to compare the success of ablation as a function of the clinical type of AF. Results: 862 pts were submitted to AF ablation (67.3% male, mean age of 58 ± 0.41 years), including 130 pts (15.1%) with LSPAF, 63.3% with paroxysmal AF and 21.6% with short-duration persistent AF (SDPAF). In LSPAF, PVI was performed with irrigated catheter in 26.4%, PVAC in 39.5% and cryoablation in 34.1%. With a mean follow up period of 838 (IQ 159-1469) days, the 3-year success rate after a single procedure was 54.1% in LSPAF, compared to 72.4% in paroxysmal AF and 61.6% in SDPAF (LogRank - p < 0.0001 - figure 1). The risk of arrhythmic recurrence was 37% higher in patients with LSPAF comparing with other groups (HR 0.63 CI 95% 0.43-0.92, p 0.016). However after a mean of 1.17 procedures/patients, the success difference between groups was not detect (LogRank – p = 0.112 – figure 2). With additional ablation procedures (REDO), the success rate at 3 years was 82.9% LSPAF pts, compared 88.2% in paroxysmal AF pts and 83.6% in SDPAF pts. In LSPAF pts, different ablation techniques did not predict arrhythmic recurrence. Regarding comorbidities, higher prevalence of peripheral arterial disease (PAD, p = 0.005) a higher NT-proBNP (p = 0.006) and left auricular volume (p = 0.045) were associated with arrhythmic relapse. Conclusions: AF ablation is more effective when performed earlier in the natural history of the disease. However, even in LSPAF pts, with additional procedures an acceptable rate of success can be achieve, independently from the ablation techniques.